2016
DOI: 10.1177/1056492616649441
|View full text |Cite
|
Sign up to set email alerts
|

Anna Hazare: A Corruption Crusader and His Grassroots Wisdom

Abstract: This paper explores the fight against corruption through the eyes of Anna Hazare, a renowned social activist from India, who spent more than 35 years of his life fighting corruption. AnnaHazare provides a detailed description of the anti-corruption movement he has led, provides his views on the World Bank guidelines to lower corruption, and highlights the need for sacrifice and righteousness on the part of leaders who fight corruption. The paper presents insights into these concepts, which deserve greater atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…From the perspective of government administrators, there are several ways to reduce opportunities and increase the risks associated with corruption to the extent that firms no longer find it profitable to engage in it, as the literature has also stressed. Stiff penalties and special entities prosecuting corruption may limit its demand side, as does increased transparency (see, for example, Chowdhury, Banerjee, & Singh Nagarkoti, 2017). Other countries have chosen to raise the salaries of administrators and regulators in an attempt to reduce the temptation to accept bribes or reward those who stand out as honest.…”
Section: Implications For Corruption Preventionmentioning
confidence: 99%
“…From the perspective of government administrators, there are several ways to reduce opportunities and increase the risks associated with corruption to the extent that firms no longer find it profitable to engage in it, as the literature has also stressed. Stiff penalties and special entities prosecuting corruption may limit its demand side, as does increased transparency (see, for example, Chowdhury, Banerjee, & Singh Nagarkoti, 2017). Other countries have chosen to raise the salaries of administrators and regulators in an attempt to reduce the temptation to accept bribes or reward those who stand out as honest.…”
Section: Implications For Corruption Preventionmentioning
confidence: 99%
“…Instead, they seem to regard such punishment as a badge of honor reflecting the power of their writings (c.f. Chowdhury et al, 2017), as shown by the survival of their ideas.…”
Section: Black Scholarship and Epistemic Injusticementioning
confidence: 99%
“…The White bystander action we propose mirrors ‘comradeship’, that is, aligning with a scientific and political struggle against inequalities (c.f. Dean, 2019), and collective intellectual activism reflects tangible ways that individuals adopt to deploy their powerful ideas for meaningful social change through just and fair deeds (Chowdhury and Willmot, 2019; Chowdhury et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…IAC activist discourse understood electoral politics as part of a corrupt nexus between politicians, public officials and business interests that betrayed the aims of the original movement for independence from colonial rule. Styling itself as a second freedom movement and deploying nationalist imagery, activists gathered behind the figurehead of the veteran social activist Anna Hazare (see Chowdhury, Banerjee, and Nagarkoti 2017). The series of spectacular protests demanding anti-corruption legislation staged by the IAC across 2011-12 (see Pinney 2014;Webb 2014;Bornstein and Sharma 2016), were made all the more forceful by being contemporary with the "Arab Spring" (Werbner, Webb, and Spellman-Poots 2014).…”
Section: The Origins Of the Aam Aadmi Partymentioning
confidence: 99%